DESKRIPSI KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS XI JASA BOGA 2 SMK N 3 PURWOKERTO - Metria Larasati (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2017)
This study aims to describe the mathematical communication abilities of students throughProblem Based Learning using a scientific approach. The subject of this research is thestudents of SMK N 3 Purwokerto class XI Foodservice 2 years 2017/2018 that add up to 32students. This type of research is qualitative, where data are collected through the studentactivity sheet on material Composition functions. Based on the results of data analysis,mathematical communication skills of students of Class XI Foodservice 2 belongs to good,just that there are 4 students that shows the result.Keywords: Mathematical Communication, Problem Based Learning, Scientific Approach,students of Class XI Foodservice SMK N 3 2 Purwokerto, composition of functions